Insulin in the Medical Management of Postprandial Hypoglycemia in a Patient with Type 2 Diabetes after Gastric Bypass Surgery - Jennifer Leung Schoenberger; Chung-Kay Koh; Tiffany Hor; David Baldwin; Arati Reddy; Lara Rondinelli-Hamilton (Case Reports in Endocrinology)
Objective. We evaluated a 47-year-old woman with a history of type 2 diabetes and severe obesity who developed postprandial hypoglycemia after undergoing Roux-en-Y gastric bypass surgery and losing 60% of her total body weight. We studied her insulin secretion and blood glucose dynamics and were able to tailor a therapeutic regimen involving insulin that eliminated episodes of hypoglycemia. Methods. We studied blood glucose levels during a prolonged fast, performed continuous glucose monitoring studies using a subcutaneous glucose sensor, and evaluated regional pancreatic insulin secretion using selective arterial calcium stimulation. Results. Continuous glucose monitoring revealed that the patient had early (1-2 hr) postprandial hyperglycemia followed by late (3-4 hr) postprandial hypoglycemia. Biochemical studies confirmed endogenous pancreatogenous insulin secretion as the cause of episodic hypoglycemia, but imaging studies and selective arterial calcium stimulation failed to localize an insulinoma. The patient was treated with preprandial doses of insulin aspart in order to attenuate the early postprandial hyperglycemia, and the late hypoglycemic episodes were avoided. Conclusion. We describe an interesting and novel nonsurgical approach to the prevention of postprandial hypoglycemia in a patient with noninsulinoma pancreatogenous hypoglycemia after gastric bypass.